Basics of anesthesia - Stoelting, Robert K; Miller, Ronald D (Churchill Livingstone, 2000)
(Churchill Livingstone) Indiana Univ., Indianapolis. Concise text for medical students, residents, and practitioners. Incorporates new information and preserves the descriptions of those practices, drugs, and monitors representing the traditional teachings in anesthesiology. Includes a new chapter devoted to opioids. Previous edition: c1994.
Keywords: anesteziologie a intenzivní lékařství